Enhanced neutrophil extracellular trap formation in COVID-19 is inhibited by the protein kinase C inhibitor ruboxistaurin. Issue 2 (4th April 2022) - Dowey, Rebecca; Cole, Joby; Thompson, A.A. Roger; Hull, Rebecca C.; Huang, Chenghao; Whatmore, Jacob; Iqbal, Ahmed; Bradley, Kirsty L.; McKenzie, Joanne; Lawrie, Allan; Condliffe, Alison M.; Kiss-Toth, Endre; et al.
Background: Neutrophil extracellular traps (NETs) are web-like DNA and protein lattices which are expelled by neutrophils to trap and kill pathogens, but which cause significant damage to the host tissue. NETs have emerged as critical mediators of lung damage, inflammation and thrombosis in coronavirus disease 2019 (COVID-19) and other diseases, but there are no therapeutics to prevent or reduce NETs that are available to patients. Methods: Neutrophils were isolated from healthy volunteers (n=9) and hospitalised patients with COVID-19 at the acute stage (n=39) and again at 3–4 months post-acute sampling (n=7). NETosis was measured by SYTOX green assays. Results: Here, we show that neutrophils isolated from hospitalised patients with COVID-19 produce significantly more NETs in response to lipopolysaccharide (LPS) compared to cells from healthy control subjects. A subset of patients was captured at follow-up clinics (3–4 months post-acute sampling), and while LPS-induced NET formation is significantly lower at this time point, it remains elevated compared to healthy controls. LPS- and phorbol myristate acetate (PMA)-induced NETs were significantly inhibited by the protein kinase C (PKC) inhibitor ruboxistaurin. Ruboxistaurin-mediated inhibition of NETs in healthy neutrophils reduces NET-induced epithelial cell death. Conclusion: Our findings suggest ruboxistaurin could reduce proinflammatory and tissue-damaging consequences of neutrophils during disease, and since it has completed phase III trials for other indications without safety concerns, it is a promising and novel therapeutic strategy for COVID-19. Proinflammatory neutrophil extracellular traps are increased during acute #COVID19 and can be reduced by the protein kinase C inhibitor and orally active drug, ruboxistaurin. https://bit.ly/3nH6sxD